Modified Mayo score Mayo score for evaluation of treatment efficacy in patients with ulcerative colitis: data from the tofacitinib OCTAVE program - William J. Sandborn; Bruce E. Sands; Séverine Vermeire; Yvette Leung; Xiang Guo; Irene Modesto; Chinyu Su; Wenjin Wang; Julian Panés (Therapeutic Advances in Gastroenterology, 2022)
Objectives: The subjectivity of the Physician Global Assessment (PGA) is a limitation of the Mayo score in assessing severity of ulcerative colitis (UC). We compared treatment efficacy using endpoint definitions based on modified Mayo (mMayo) score, versus those based on Mayo score, using data from the tofacitinib OCTAVE program. Design: This post hoc analysis included data from two 8-week induction studies (OCTAVE Induction 1 and 2) and a 52-week maintenance study (OCTAVE Sustain). Methods: Remission and clinical response [with nonresponder imputation (NRI)] were assessed using mMayo (without PGA) and Mayo scores, and further stratified by prior tumor necrosis factor inhibitor (TNFi) failure status. Results: At week 8 of OCTAVE Induction 1 and 2, remission rates with placebo and tofacitinib 10 mg twice daily (BID), respectively, were 7.7% and 24.8% (mMayo) and 6.0% and 17.6% (Mayo). At week 52 of OCTAVE Sustain, remission rates with placebo, tofacitinib 5 and 10 mg BID, respectively, were 12.1%, 35.9%, and 42.1% (mMayo) and 11.1%, 34.3%, and 40.6% (Mayo). A statistically significant ( p  < 0.05) treatment effect of tofacitinib versus placebo was observed for remission and clinical response at all time points, regardless of scoring definition or prior TNFi failure status. Conclusions: A significant effect of tofacitinib versus placebo was demonstrated across efficacy endpoints using mMayo score, consistent with previously reported data using Mayo score. Treatment effect sizes were generally similar regardless of scoring definition. This observation may help contextualize tofacitinib therapy outcomes with those of new UC therapies and support the use of Mayo score-based endpoints in UC clinical trials. Trail registration: ClinicalTrials.gov identifiers: NCT01465763; NCT01458951; NCT01458574.